1993
DOI: 10.1080/01652176.1993.9694361
|View full text |Cite
|
Sign up to set email alerts
|

A sero‐epizootiological study of porcine respiratory coronavirus in belgian swine

Abstract: SUMMARYA porcine respiratory coronavirus (PRCV), antigenically closely related to transmissible gastroenteritis virus (TGEV), appeared in the European swine population in 1984. The present serological study was performed to obtain insight into the epizootiology of PRCV and of TGEV PRCV-induced neutralizing antibodies were found in 90.6 per cent of the 160 sera collected from sows at slaughter, demonstrating the enzootic appearance of PRCV in the Belgian swine population. A serological study of fattening swine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…Several experimental studies have reported that PRCV can induce a variable degree of protection against TGEV infection [1,3,9,18,19]. Taken together with our data, these findings suggest that the recent decrease in epidemic TGE outbreaks in Japan may have resulted from widespread infection of PRCV, as observed in European countries [10,12,13]. On the other hand, in our study, TGEV antibody-positive pigs were found at several PRCV antibody-positive farms; furthermore, a TGE outbreak occurred at one of these farms, although the reason for the outbreak was unclear.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Several experimental studies have reported that PRCV can induce a variable degree of protection against TGEV infection [1,3,9,18,19]. Taken together with our data, these findings suggest that the recent decrease in epidemic TGE outbreaks in Japan may have resulted from widespread infection of PRCV, as observed in European countries [10,12,13]. On the other hand, in our study, TGEV antibody-positive pigs were found at several PRCV antibody-positive farms; furthermore, a TGE outbreak occurred at one of these farms, although the reason for the outbreak was unclear.…”
supporting
confidence: 78%
“…The incidence and severity of TGE have decreased markedly since the widespread infection of PRCV in European swine herds in the late 1980s to early 1990s [10,12,13]. In the United States, a decrease in TGE incidence has been reported in one area having a high prevalence of PRCV antibody [20,21]; in other TGEV-and PRCV-seronegative herds, however, TGE remains a major cause of sickness and death in piglets [14,15].…”
mentioning
confidence: 99%
“…PRCV has spread widely in the European swine population (reviewed in [4]). In 1989-1990 up to 90.6% of the pigs in Belgium were seropositive for PRCV [5]. At present, more than 95% of the Belgian swine herds are seropositive against PRCV (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Porcine respiratory coronavirus (PRCV) is ubiquitous in Europe and appears to have become increasingly prevalent in swine herds in North America [1,2]. In Belgium, most pigs become infected between 6 and 15 weeks of age, and antibodies to PRCV are prevalent in c. 90% of pigs at slaughter.…”
Section: Introductionmentioning
confidence: 99%